Multi-level DLD microfluidic chip for plasma separation: A novel approach using Cu-ACE - Milad Darboui; Meysam Fatehi; Reza Zareifar; Hamid Reza Taheri Tolgari; Hadi Esmaeili Khoshmardan (Results in Physics)
This paper presents the design and fabrication of an innovative microfluidic chip inspired by the intricate mechanism of fish gills. The main objective of this study is to develop an efficient microfluidic chip for the selective separation of blood plasma. To this end, numerical simulations in COMSOL Multiphysics software have been employed to optimize geometric and operational parameters, thereby achieving optimal separation efficiency. The fabrication of this chip employed the copper-assisted chemical etching (Cu-ACE) technique, resulting in the formation of a well-ordered array of crescent-shaped micro holes on a silicon wafer. The micro holes were molded using polydimethylsiloxane (PDMS), resulting in the production of PDMS pillars in a deterministic lateral displacement (DLD) structure. These filters were integrated into a copper reservoir with a depth of 10 μm, then strong bond between the PDMS structure and copper substrate was established using a new self-assembled silane layer. To assess the surface morphology and quality of the fabricated structures, field emission scanning electron microscopy (FE-SEM) and optical microscopy (OM) were utilized to observe the separation of the cells from the plasma. A hemocytometer was provided to determine the purity percentage for validation and assessment of the results. The results indicated that the adhesion between PDMS and copper is acceptable. Additionally, the crescent-shaped pillars have an efficient effect on the separation, achieving a plasma purity of 98 % from experimental test.